2015
DOI: 10.1515/jpem-2014-0364
|View full text |Cite
|
Sign up to set email alerts
|

An increasing incidence of type 1 diabetes mellitus in Romanian children aged 0 to 17 years

Abstract: Romania is a country with an intermediate incidence of type 1 diabetes mellitus in children, which is slightly higher in boys than in girls. The incidence of type 1 diabetes mellitus increased continuously during the 10-year survey, with the exception of the oldest teens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 17 publications
4
13
0
2
Order By: Relevance
“…Alongside the inherited causes of HTG, the most important predisposing factors are high lipid and carbohydrate intake, lack of physical activity, and obesity 12. The negative impact that the metabolic syndrome (MS), dysglycemia, and abdominal obesity have on the level of TG is very well known 2123.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alongside the inherited causes of HTG, the most important predisposing factors are high lipid and carbohydrate intake, lack of physical activity, and obesity 12. The negative impact that the metabolic syndrome (MS), dysglycemia, and abdominal obesity have on the level of TG is very well known 2123.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus (DM) is a chronic, heterogeneous disease with a progressive evolution and multiple complications, its incidence being cited to have an important increase in the latest years 12. Besides the two main types of diabetes (type 1 and type 2), secondary types have been identified, among which one of the leading causes is represented by pancreatic diseases such as AP, chronic pancreatitis (CP), cystic fibrosis, or pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Diabetes mellitus (DM) is nowadays a major public health issue, with continuously increasing prevalence in both of its major two components: type 1 (T1DM) and T2DM 1,2. It is estimated that nowadays, 415 million adults are living with T2DM and that this number will increase to 642 million in 2040 1.…”
Section: Background and Aimsmentioning
confidence: 99%
“…Tao et al [12] proved that the prevalence of type 1 diabetes has been increased by 2-5% worldwide and its prevalence is approximately one in 300 in the USA by 18 years of age. Similarly, Serban et al [13] found the mean incidence being highest in the age group 10-14 years and the raise in incidence was noticed in all age groups except for 15-17 years.…”
Section: Discussionmentioning
confidence: 67%